Implementasi Model Pembelajaran Flipped Clasroom dalam Pembelajaran Bahasa Indonesia: Kajian Systematic Literature Review: Implementation of Flipped Classroom Learning Model in Indonesian Language Learning: Systematic Literature Review - Sutrisna, I Putu Gede; Sutama, I Made; Dewantara, I Putu Mas; Wirahyuni, Kadek (ITScience (Information Technology and Science), 2024)
21st-century education requires students not only to understand content but also to be able to think critically and solve problems. Innovation in learning strategies is needed to increase student engagement and understanding. The flipped classroom learning model is here to overcome this. The flipped classroom-based learning model is a student-centered learning model that increases learning effectiveness. Thus, it is necessary to conduct a study on the flipped classroom learning model to improve students' critical thinking skills. This study aimed to determine the results of a literature review study on implementing the flipped classroom model in Indonesian language learning. The SLR (Systematic Literature Review) method was chosen in this study. Data was collected by documenting and reviewing all articles on Indonesian language learning outcomes with the flipped classroom learning model. A total of 10 articles in the last 5 years obtained from Google Scholar and other sources were used in this study. Based on the literature review, there is an increase in students' critical thinking with the application of the flipped classroom model in Indonesian language learning. This is due to supporting factors: using the flipped classroom learning model and interactive learning media. Implementing the flipped classroom learning model can improve students' critical thinking skills in Indonesian language learning. Educators can use this model as a learning innovation to achieve learning objectives quickly.